(untitled) (Global Journal of Human-Social Science, 2021)
The main objective of this study is to assess the effects of COVID-19 on household income and food security in Cameroon. In this evaluation, the data used was collected using an online questionnaire sent to random respondents using social networks (Whatsapp, Facebook and Telegram). This data appropriation strategy proved to be the best method in the presence of the process of social distancing which did not allow the possibility of conducting the interviews face to face. We use the recent methodology developed by Kansiime et al. (2020). Our online questionnaire was open over a period of 15 days, from March 17 to 31, 2020. The choice of this period is dictated by the start of the containment measures adopted by the Cameroonian Government. According to the answers obtained, 303 and 250 people respectively in the cities of Yaoundé and Douala answered this questionnaire for a total of 553 respondents. To estimate whether a respondent’s source of income has been affected by COVID-19 and whether the diet has deteriorated, the PROBIT regression model is used. The results obtained show that ceteris paribus: (i) the farmer is 55% more likely to experience the negative effects of COVID-19 on his source of income. (ii) salaried employment is 65% less likely to be adversely affected by COVID-19 on their food security.